Association and Linkage Disequilibrium Analyses of APOE Polymorphisms in Atherosclerosis. Issue 2 (2008) - Artieda, Marta; Gañán, Alberto; Cenarro, Ana; García-Otín, Ángel Luis; Jericó, Ivonne; Civeira, Fernando; Pocoví, Miguel
Abstract : Background : Apolipoprotein E (apo E) plays a major role in lipid metabolism, and its genetic variations have been associated with cardiovascular risk. The objective of this study was to investigate the influence of the APOE promoter (−491 A/T, −427 T/C and −219 G/T) and coding region ( APOE ɛ2/ɛ3/ɛ4) polymorphisms in atherosclerosis disease by association and linkage disequilibrium analyses. Materials and methods: We analyzed these polymorphisms in a sample of 286 subjects with atherosclerosis disease: 153 subjects with atherothrombotic stroke (ATS) and 133 subjects with ischemic heart disease (IHD); and in two control groups, 103 newborns and 114 elderly subjects. Results : The ɛ4 allele was associated with more severe carotid stenosis in the ATS group, being the percentages of ɛ4 carriers 26.7% and 11.4% for the higher and lower carotid stenosis groups, respectively ( p =0, 066). The −491 T/T IHD subjects presented higher vessel scores than subjects A/A and A/T genotypes at that position (p=0, 041), and the frequencies of −2 (5.1% versus 14.1%, p =0, 060) and −427C (10.3% versus 24.4%, p =0, 019) alleles were lower in IHD subjects with higher extent score versus lower extent score. The ɛ2 allele was in linkage disequilibrium with the −427C allele in all studied groups, and the −219T allele was associated with the ɛ4 allele in the IHD group. Conclusion : In summary, the ɛ2 allele was in linkage disequilibrium with the −427C allele in all studied groups, and only slight associations between the analyzed APOE polymorphisms in the promoter and in the coding region and carotid and coronary vascular disease have been observed.